DIAGRAM FAKTOR KONSENTRASI TEGANGAN PADA PERCABANGAN PIPA 90* AKIBAT TEKANAN INTERNAL DENGAN METODE ELEMEN HINGGA - Aris Gunara, Martinus
Abstract: Stress Concentration Factor (SCF) at cross-sectioning pipe is defined as ratio between actual principal stress and nominal stress of pipe. The formulas are as follows : SCF = 6 maks = PD a\'nom ---- 2T Stress Concentration Factor (SCF) diagrams respective with variables of cross-section pipe has not provided adequately. Once actual principal stress or SCF required, practically it has to perform numerical calculation by using finite element method to find out it. This thesis is trying to expose that idea by providing stress concentration diagrams respective with variables of cross-section pipe such as main pipe diameter (D), branch pipe diameter, main pipe thickness (T) and branch pipe thickness (t). The angle between main pipe and branch is constant of 90* . This cross-section pipe structure is simply supported and loaded by internal pressure. SCF calculation was done using MSC Nastran/Patran software as finite element method application. SCF value can be determined easier by using SCF diagrams instead of using calculation by finite element method.